Disability, work, and cash benefits - Mashaw, Jerry L. (W.E. Upjohn Institute for Employment Research, 1996)
Reviews the US Social Security disability programme, with a view to determining whether rehabilitation and work could be incorporated in the income programme without greatly expanding costs or weakening the right to benefit for disabled persons.
Papers presented at a conference on disability, work, and cash benefits held December 8-10, 1994 in Santa Monica, California, jointly sponsored by National Academy of Social Insurance and the National Institute on Disability and Rehabilitation Research of the U.S. Department of Education.
Keywords: People with disabilities -- Employment -- United States -- Congresses.; Disability insurance -- United States -- Congresses.; Social security -- United States -- Congresses.; Vocational rehabilitation -- United States -- Congresses.; Sheltered workshops -- United States -- Congresses.; Employee fringe benefits -- United States -- Congresses.; Labor market -- United States -- Congresses.; People with disabilities -- Employment -- Law and legislation -- United States -- Congresses.; Personnes handicapées -- Travail -- États-Unis -- Congrès.; Assurance-invalidité -- États-Unis -- Congrès.; Sécurité sociale -- États-Unis -- Congrès.; Réadaptation professionnelle -- États-Unis -- Congrès.; Ateliers protégés -- États-Unis -- Congrès.; Avantages sociaux -- États-Unis -- Congrès.; Marché du travail -- États-Unis -- Congrès.; Personnes handicapées -- Travail -- Droit -- États-Unis -- Congrès.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Disability insurance; Employee fringe benefits; Labor market; People with disabilities -- Employment; People with disabilities -- Employment -- Law and legislation; Sheltered workshops; Social security; Vocational rehabilitation; United States; disability benefit.; workers with disabilities.; cash benefit.; fringe benefit.; vocational rehabilitation.; work incentive.; social cost.; social policy.; employment policy.; employment opportunity.; return to work.; sheltered workshop.; private sector.; autonomy of people with disabilities.; USA.; Western Europe.; prestations d'invalidité; travailleur handicapé; prestations en espèces.; avantages accessoires.; réadaptation professionnelle.; incitation au travail.; coût social.; politique sociale.; politique de l'emploi.; possibilités d'emploi.; réinsertion professionnelle.; atelier protégé; secteur privé; autonomie du handicapé; Etats-Unis.; Europe occidentale.; prestaciones de invalidez.; trabajador con discapacidad.; prestaciones monetarias.; prestaciones no salariales.; rehabilitación profesional.; incentivo al trabajo.; costo social.; política social.; política de empleo.; oportunidades de empleo.; reinserción profesional.; taller protegido.; sector privado.; autonomía de las personas con discapacidad.; Estados Unidos.; Europa Occidental.; Conference papers and proceedings; conference paper.; bibliography.; document de conférence.; bibliographie.; documento de conferencia.; bibliografía.